VERTICAL JUMP HEIGHT IN YOUNG CHILDREN - A LONGITUDINAL STUDY IN 4- TO 6-YEAR OLD CHILDREN - Katja Koren; Rado Pišot; Boštjan Šimunič (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2017)
Preschool children are intensively involved in the process of developing fundamental movement skills such as walking, running, jumping, climbing, crawling and other simple movements. We aimed to compare age- and gender- related trends in countermovement vertical jump (CMJ) performance (jumping height) measured with a means of ground force plate during a longitudinal study of 4- to 6-year old children (N=79; 43% boys). Furthermore, we classified children CMJ arm-leg coordination into poor, average, or excellent on the grounds of high speed video footage. We found that CMJ height progresses significantly with age when arms are used (P<.001, η2=.632) and without the use of arms (P<.001, η2=.620). There were no sex effects. After classification of CMJ arm - leg coordination we found that children with excellent CMJ coordination progress more intensively than those with average coordination, whereas poorly coordinated jumpers do not progress at all. After extrapolating our data with the data of others, we found logarithmic CMJ height trends until the age of 16 in both sexes, athlete boys jumping higher than the non-athletes after the ages of 14 or 15. It seems that the initial movement patterns level, in this case the observed jumping technic, develops and refines in 4- to 6-year old children at that age. We conclude that jumping coordination is a very important factor of CMJ performance in the studied age span.